Discontinuity controlled slope failure zoning for a granitoid complex: A fuzzy approach - Gurocak, Z.; Alemdag, S.; Bostanci, H.T.; Gokceoglu, C. (Taylor and Francis, 2017)
Kinematic analysis is one of the most used methods to evaluate potential failures such as planar, wedge and toppling in rock slopes. To analyze possible failure types, orientations of slope and discontinuity geometry with the friction angle of the discontinuities planes are used. In this study, kinematical analyses were evaluated to obtain discontinuity controlled potential failure types in the Gumushane Granitoid Complex which is exposed in Gumushane City and the surroundings. Unstable slope orientations for planar, wedge and toppling failure types were determined. The unstable orientations obtained from kinematic analyses were used to create Geographic Information System (GIS) based instability risk maps. The maps generated by the GIS were evaluated using the Fuzzy Interference System (FIS) method to produce instability risk maps for the study area. © 2017 Taylor & Francis Group, London, UK.